2018
DOI: 10.1038/s41586-018-0789-4
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic synaptic plasticity underlying compulsion in a model of addiction

Abstract: Activation of the mesolimbic dopamine system reinforces goal-directed behavior. With repetitive stimulation, for example by chronic drug abuse, the reinforcement may become compulsive and intake continues even when facing major negative consequences. Here we gave mice the opportunity for optogenetic dopamine neuron self-stimulation (oDASS) and observed that only a fraction of mice persevered if they had to endure an electric shock. Compulsive lever pressing was associated with an activity peak in orbitofrontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
136
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 48 publications
16
136
3
Order By: Relevance
“…However, in this study, no distinct subpopulations of rats emerged, and the ratio of addicted animals remains to be determined. By contrast, using the same seek-take chain paradigm, we found a similar ratio of persevering mice that the one obtained when the taking lever was punished (Pascoli et al, 2018).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, in this study, no distinct subpopulations of rats emerged, and the ratio of addicted animals remains to be determined. By contrast, using the same seek-take chain paradigm, we found a similar ratio of persevering mice that the one obtained when the taking lever was punished (Pascoli et al, 2018).…”
Section: Discussionsupporting
confidence: 62%
“…Compulsive SA may also reflect a deficit of inhibitory control, where drug seeking despite punishment persists due to the hypofunction of mPFC (Chen et al, 2013). By contrast, we have found a hyperactivity of the OFC to DS projection in mice complusively self-stimulating VTA DA neurons (Pascoli et al, 2018;, suggesting a decision making bias favoring reward pursuit despite the risk of punishment.…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…revealed that the OFC is necessary for using expectations of specific outcome to guide behavior and learning 3,59 . The outcome predictions signaled by the OFC neurons could be utilized by downstream regions such as ventral striatum 60,61 , dorsal striatum 60,62 , BLA 63 and VTA 23,29,64 . OFC lesion or inactivation disrupted the prediction errors signaled by dopaminergic neurons 29,64 and expected reward values by putative non-dopaminergic neurons 64 in VTA.…”
Section: Studies Using Outcome Devaluation and Pavlovian Over-expectamentioning
confidence: 99%
“…Besides neurons, synapses are also stochastic in cerebral cortical [8]. Formation, elimination and volume change of dendritic spines exhibit random fluctuation [9][10][11][12][13][14][15] and transmitter release from synapses is also inherently unreliable [16][17][18]. These stochastic features may realize nearly optimal computation and learning under uncertain environment via Bayesian inference [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%